Local Income Taxes in Sweden - Hanousek, Kryšpín (2024)
This thesis aims to analyze the relationship between the internal migration flows in Sweden and the tax rate differential between the Swedish regions using multiple regression analysis. Abstract: While the inherent motivation behind migration may differ on a personal level, there are common factors considered when choosing the final destination – labor opportunities, housing costs, income, weather conditions, family environment, and also tax conditions. Tax rate has been identified among the significant factors influencing the selection of the location where to go in regards to external migration, but except for a few studies performed over a decade ago, the current research on the relationship between tax and internal migration is quite limited. With one of the most mobile populations in Europe and a unique tax system, where the personal income tax rate due to the fiscal decentralization varies between the municipalities and counties, Sweden shows potential for assessing the impact of tax rate differential between the regions on the internal migration flows. Using macroeconomic data on the internal migration flows between the counties in Sweden from 2010 and 2020, this research is focused on identifying the potentially influential effect of tax rate differential on the probability of inmigration into a particular county within Sweden. Being aware of the presence of other decisive factors, the regression analysis includes additional independent variables to be controlled for and thus helps to isolate the effect of the tax rate differential on the probability of inmigration into a county.